AKUNTABILITAS PENGELOLAAN DANA DESA DALAM PENCEGAHAN TINDAK PIDANA KORUPSI - Yustika Mahdania; Aminuddin Ilmar; Audyna Mayasari Muin (JURNAL ILMIAH LIVING LAW, 2022)
This research aims to analyze the accountability of village fund management as a prevention of corruption in the accountability of village fund management. and analyze the form of supervision in accountability of village fund management as a prevention of corruption crimes. This type of research is a normative method, using a case approach. The results of the study show that: Accountability of village fund management in preventing corruption can be seen from performance measurement, performance management, and performance budgeting. In the management of village funds, there are still frequent misuse of village funds for the personal interests of village government elements. The form of supervision in the accountability of village fund management in preventing corruption through preventive supervision and repressive supervision. In reality, the rules related to the form of supervision have been regulated by involving various parties. However, in practice there are still many village government elements who easily misuse village funds.